Method For Determining The Minimum Number Of Sorting Routes Depending On The Length Of Wagon Groups - Sh.M. Suyunbaev; Sh.B. Jumaev; Sh.Sh. Kayumov (Genius Journals, 2021)
Currently, the formation of multi-group freight trains in accordance with the established procedure at all marshalling yards of JSC “O‘zbekiston temir yo‘llari” is carried out on the basis of the experience of the relevant personnel. Therefore, one of the urgent tasks is to improve the process of forming such trains based on the introduction of information technologies. This article analyzes the number of train assignments by type in terms of train formation and concludes that due to a decrease in the share of singlegroup trains by 93% over the past 5 years, the share of multi-group trains has increased by 31%. A method has been developed for determining the minimum required number of marshalling tracks depending on the length of a group of wagons using the Fibonacci number, and the results of the implementation of the developed method at the Chukursay marshalling yard are shown
Keywords: Train formation plan; single-group trains; multi-group trains; modular train